Is technology optimism justified? A discussion towards a comprehensive narrative. (20th June 2019) - Gonella, F.; Almeida, C.M.V.B.; Fiorentino, G.; Handayani, K.; Spanò, F.; Testoni, R.; Zucaro, A.
Abstract: This paper is based on a discussion developed by one of the thematic working groups at the Biennial International Workshop Advances in Energy Studies (BIWAES) 2017 hold in Naples, Italy. The topic was the role of technology in energy transition and global problems. Owing to the heterogeneity of the participants in the working group, different viewpoints were put together, leading to some shared conclusions. In particular, the role played by the different narratives used in discussing the role of technology in facing global problems was pointed out as the origin of cognitive dissonance. The presented reflections address some conceptual weaknesses in the current debate on technology and global issues, framed in global policies that appear incapable to obtain tangible results. The technology optimism seems, in fact, to be based on the elusive use of both the concepts of technology and sustainability, that are put together for narrative purposes without an explicit conceptual assessment. On one hand, the factual role of technology and its beneficiary are almost never clearly addressed in the debate. On the other hand, the fact that any new technology will serve the cause of sustainability is not questioned whatsoever, without taking into account the social, political and ethical framework in which technology is supposed to be operated. Highlights: Thematic working groups at the BIWAES 2017 Conference. Conceptual weaknesses in the current debate on technology are addressed. The questions "Technology for what?" and "Technology for whom?" are mandatory. There is a strong need for a correct contextualization of technology debate. A shared and openly-described narrative is mandatory.